Variation in zooplankton prey distribution determines marine foraging distributions of breeding Cassin's Auklet. (November 2017) - Bertram, Douglas F.; Mackas, David L.; Welch, David W.; Boyd, W. Sean; Ryder, John L.; Galbraith, Moira; Hedd, April; Morgan, Ken; O'Hara, Patrick D.
Abstract: To investigate the causal basis for patterns of seabird foraging distributions during breeding we integrated data from ship-board seabird and zooplankton surveys, aerial radio telemetry, and colony-based research programs. We examined the marine distributions of Cassin's Auklet ( Ptychoramphus aleuticus ) breeding on Triangle Island, in the Northeast Pacific off the coast of B.C., Canada using surveys conducted in 1999, 2000, and 2001. Concurrently, we sampled zooplankton at 16 stations along a cross shelf transect in the vicinity of Triangle Island. In 1999 and 2000, when populations of the preferred copepod prey Neocalanus cristatus were available at deep-water stations (1000–2000 m), the majority of the auklets were concentrated SW of the colony 40–75 km offshore and parallel to, but 35 −50 km beyond the shelf break in deep water (1200–2000 m). Birds did not fly farther out to sea to where prey was five times more abundant when N. cristatus could be found at lower abundance levels, closer to the colony. In 2001, N. cristatus were virtually absent at the deep-water stations, likely as a result of massive salp (family Salpidae) aggregations which may have consumed and displaced the seabirds' preferred prey. We demonstrate that while birds were still able to locate and provision chicks with N. cristatus in 2001, they had to forage farther away from the colony in order to do so. Our telemetry results are generally consistent with analyses of at-sea distributions of Cassin's Auklets derived from ship-board surveys (1990–2010) both of which have contributed to the design of the proposed Scott Islands marine National Wildlife Area, the first of its kind in Canada. Highlights: Birds did not fly farther out to sea to where prey was five times more abundant when N. cristatus could be found at lower abundance, closer to the colony. Telemetry results were generally consistent with analyses of at-sea distributions of Cassin's Auklets based on ship-board surveys (1990-2010). This is the first time in Canada that seabird foraging distributions have contributed to the design of a marine protected area.